TIKAS: Kindergarten Attendance Application with Role-Based Access Control for Tadika Inovasi Kreatif - Samsudin, Nur Hazwani Hanum; Ab Rahman, Nurul Hidayah (Applied Information Technology And Computer Science, 2024)
This attendance application (TIKAS) is developed for Tadika Inovasi Kreatif to record the attendance of the students and generate an annual report of attendance. The classified information breach and altered by the unauthorized access motivates the direction of developing TIKAS with automated attendance management. If the student is absent, the parent can easily key in the reason for the absence in the attendance form. Therefore, this study proposed TIKAS to only allow authorized users to enter the application by applying role-based access control (RBAC). Multifactor authentication using One Time Password is also applied to provide secure authentication process to TIKAS. The methodology employed in this application is agile model which consists of six phases: planning, analysis, design, implementation, testing, and deployment. This application was developed using Android Studio as the Integrated Development Environment (IDE), Java programming language, and Firebase as a database. As a result, TIKAS is developed with six modules that are: dashboard, login, register, manage account, parent management, teacher management, and attendance management. The access control to the modules is defined using three role-based that are system admin, teacher, and guardian/parents. Thus, the significance of the study is to prevent a violation of access control to the application and ease the process of recording attendance.